Comparison of antimicrobial prescribing patterns with the standard treatment guidelines and essential drug list in primary healthcare facilities in Vhembe district,Limpopo Province. - Mulatedzi, Makhado (University of Limpopo (Medunsa Campus), 2009)
Background: The study was conducted in primary healthcare facilities in Vhembe district in Limpopo province, South Africa. Seeing that the National Drug policy was implemented in 1996 and followed by the Standard Treatment Guidelines, it was necessary to investigate if PHC facilities are prescribing according to the guidelines. Although the data collected was from five clinics, iinformation on antimicrobial prescribing patterns is necessary for a constructive approach to the challenges that arise from the vast number of antibiotics that are available in the market and the occurrence of resistance. Objectives: The aim of the study was to investigate whether prescribers at Primary Health Care (PHC) facilities in Vhembe district adhered to the Standard Treatment Guidelines/Essential Drug List (STG/EDL) when prescribing antimicrobials. Method: Five hundred antimicrobial prescribing patterns and patient demographics were recorded from five PHC facilities (100 prescriptions in each) in the Vhembe District, Limpopo Province over a two weeks period. In all PHC facilities, data collection of prescriptions focused on the period from 01 August 2007 until the required number of 100 prescriptions was reached. x Results: Conditions where prescriptions complied to STG/EDL were skin infections and wound 91.67% (22/24), upper respiratory tract infection 86.49% (32/37), bronchitis 80% (4/5), ear/eye infections 75% (3/4), otitis media 57.14% (4/7), sore throat/tonsillitis 56.57% (56/99), urinary tract infection 37.5% (3/8), sexual transmitted infections 37.25% (19/51), bites 33.33% (1/3), and abscesses 25% (1/4). All other remaining 18 conditions that were listed as diagnosis did not comply at all. On overall only 29.2% (146/500) of prescriptions that were evaluated complied. Conclusion: Antimicrobial prescribing patterns adhering to the EDL/STD were low. Attention needs to be given to the prescribing of antimicrobials.
Thesis (Msc.(Med.)(Pharmacy))--University of Limpopo, 2009.
Keywords: Antimicrobial prescribing patterns.